Design of artificial landmarks for underwater simultaneous localisation and mapping. Issue 1 (1st January 2013) - Pailhas, Yan; Capus, Chris; Brown, Keith; Petillot, Yvan
Abstract : The use of autonomous underwater vehicles for a variety of purposes is set to increase in the future. A key issue is accurate navigation, especially for survey applications large cumulative error are introduced by the various position sensors: accelerometer; Doppler velocity log; compass; inertial navigation sensors. Algorithms such as simultaneous localisation and mapping rely on accurate landmark recognition in order to correct the vehicle position. This study proposes a solution based on broadband sonar and passive artificial coded landmarks to improve the navigation. Through resolution of the wave equation for acoustic propagation in a multilayer concentric sphere, it is shown that there is a great diversity in the echo spectrum with only small changes in internal structure. This enables the design of a set of passive landmarks, which can be identified unambiguously, since each has a characteristic signature or spectral code when insonified with a broadband sonar.